Mai’a K. Davis Cross, Ireneusz Paweł Karolewski (red.), European-Russian Power Relations in Turbulent Times, University of Michigan Press, Ann Arbor 2021, ss. 311. - Podraza, Andrzej (Rocznik Integracji Europejskiej, 2021)
Recenzja